The Evolving Structure Hospitals in the United States and the Growth of Multi-Hospital Systems, 2011 – 2021 - Melnick, Glenn A (British Journal of Healthcare and Medical Research, 2024)
A large segment of the United States (US) health care system relies heavily on competitive market forces to drive the performance of the system. This aspect of the US health care system is based on the premise that competition and market forces can improve the efficiency and quality of health care delivery. Researchers and policy analysts are increasingly concerned about structural and other changes that might undermine competitive market conditions and reduce the effectiveness of the US health care system, especially concerning hospital services. This paper provides a descriptive analysis of the development, growth, evolution, and structure of US hospitals with a focus on the growth of multi-hospital systems over an extended period and discusses some of the implications of these trends. The data presented here show a trend of increased concentration of hospital bed capacity within multi-hospital systems, raising anti-competitive concerns. A high concentration of hospital bed capacity within multi-hospital systems can reduce competitive forces, leading to higher prices for health care services. Our findings collectively suggest a complex landscape of hospital service delivery, ownership, and increased consolidation including the expanded role of multi-hospital systems in the US and underscore the importance of monitoring these trends and implementing policies and regulations to ensure efficient pricing, access, and quality of care while accommodating a changing health care landscape. While this paper applies largely to developments in the US health care system, there may be lessons from other countries, especially those countries that rely in part on competitive market forces to drive the performance of their systems.